Child sexual abuse (rape) in Anambra state: South Eastern Nigeria - Ajaegbu, Obinna C.; Madubuike, Chinelo N.; Ezeonwu, Bertila U.; Uchendu, Bernadette U.; Obidike, Afam; Ajaegbu, Faith N. (International Journal Of Community Medicine And Public Health, 2023)
Background: Child sexual abuse (CSA) which is an infringement of the child’s fundamental human right has assumed a public health importance due to increasing prevalence globally and Nigeria in particular. This problem not only possess immediate complications like unwanted pregnancy, sexually transmitted infections (STI) and others, but the long term impact on the child’s mental-health is enormous. This study is aimed at documenting the burden of this problem in Anambra state and interventions to mitigate it. Methods: This was a prospective study of all the children who presented to the Ntasi Sexual Assault Reference Center (SARC), Anambra State with history of sexual abuse from September 2019 to August 2020. Results: A total of 820 children were seen during the study period, 81 (9.8%) were diagnosed to have been sexually abused. There were 69 (85.3%) female and 12 (14.8%) male giving a female to male ratio of 5:1. The incidence of the abuse increased with increasing age of the subjects and peaks at those aged 11-15 years, 28 (34.6%). Sixty-nine (85.2%) were abused once while 12 (14.8%) were abused multiple times. Most of the abuse took place in the perpetrators home 47 (38.8%) followed by uncompleted building 14 (11.6%). Vaginal penetration 69 (85.2%) was the commonest form of sexual abuse seen followed by anal penetration 12 (14.8). Conclusions: Child sexual abuse remains a major public health problem with high rate of under-reporting. Heath education, free medical care to victims and government strong political will are needed in curbing this menace.